Effect of Magnesium Sulfate on the Total Anesthetic and Analgesic Requirements in Neurosurgery - Essam Manaa (Journal of Spine Practice)
Introduction: The intraoperative anesthetic and postoperative analgesic requirements are of great importance especially in neurosurgical anesthesia. This requires balancing a deep and effective anesthesia and postoperative analgesia versus the risks of delayed recovery and postoperative respiratory depression from excessive analgesics. Magnesium sulfate is an antagonist of the N-Methyl-D-Aspartate (NMDA) receptors in a voltage-dependent fashion. Propofol also inhibits the NMDA subtype of the glutamate receptor. Therefore, magnesium sulfate when coadministered with propofol potentiates anesthetic effect and NMDA antagonism of propofol. Majority of the studies that evaluated the anesthetic and analgesic requirement in patients receiving magnesium sulfate depended on the clinical parameters, for example, hemodynamic parameters and measurement of pain scores. In this study, we added bispectral index (BIS) and neuromuscular monitoring using train-of-four (TOF) to adjust intraoperative anesthetic requirements in addition to the clinical parameters.